IMPACT OF DIGITALIZATION IN THE MARKETING OF GEOGRAPHICAL INDICATION PRODUCTS WITH SPECIAL REFERENCE TO ARANMULA KANNADI - MANOJ .M Dr. A.SULEKHA (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Digitalization has become the order of the day in most developed and developing countries. The process of converting data into a digital format is called digitalization. The world has now become a digital village. Digital Marketing is an experiment in marketing segment. Aranmula Kannadi is a Geographical Indication product. It is a handcrafted metal combination mirror, made in Aranmula, a small residential area in Kerala state. The purpose of the study was to analyze the influence of digitalization in the sales of Aranmula Kannadi. The study conducted on thirty producers of Aranmula Kannadi. The data has collected by distributing the questionnaires among the selected producers. Descriptive statistics was used to analyze the demographics and ‘t’ test was used to analyze the research objectives. The result of the study showed that digitalization helps to improve the sales of Aranmula Kannadi significantly.